Avatar, the last airbender. North and south. Part one - Yang, Gene Luen (Dark Horse Books, 2016)
Siblings Katara and Sokka struggle to get used to changes in their once-humble village, with Gran Gran being married, new construction projects, and Hakoda being made chief of the entire tribe. All this seems the work of Northern Water Tribe member Malina, but her true goals in unifying the North and South seem shady.